KONSTRUKSI PENDIDIKAN KARAKTER SISWA MELALUI KETELADANAN GURU DI SEKOLAH - Siti Qurratul Aini; Faizin Syamwil (Perkumpulan Manajer Pendidikan Islam (PERMAPENDIS) Indonesia, 2020)
This paper analyzes the construction of student character education through exemplary education in elementary schools. The research approach used is a qualitative with library research. The data analysis technique uses content analysis. The results showed that elementary schools are the most effective place to build student character education, considering that at this age it is a golden age, and they have a strong memory for remembering everything they see and feel. Building character education at this time, will be effective, if the teacher puts himself as an individual figure who is a good example for students. Teacher modeling will have a positive impact on student development and affect the formation of students' character and personality, both in the aspects of behavior, attitudes and habits in the school environment and in the wider environment